Epidemiology of notifiable outbreaks in different hospital units in Saudi Arabia: A national descriptive study - Nawal M. Alanazi; Nasser H. Alshanbari; Hala M. Roushdy; Yahya I. Alnshbah; Eman Ali Barnawi; Nawaf M. Almatrafi; Rula Felemban; Zainah M. Al Shahrani; Nadeen Burhan; Aiman El-Saed; Khalid H. Alanazi (Journal of Infection and Public Health)
Background: Healthcare-associated outbreaks have serious impacts on patient morbidity and mortality, and healthcare resources. The objective was to describe the epidemiology of healthcare outbreaks notified to the Saudi Ministry of Health (MOH) over a year. Methods: A retrospective analysis of national data collected through timely notifications to the MOH during 2023. Data included hospital and patient information. Healthcare outbreaks were defined as per the MOH outbreak manual. Outbreaks notified by 117 MOH hospitals and 53 private hospitals in 20 Saudi regions were included. Results: A total of 1240 outbreaks were notified, including 2392 patients, 2703 infections, and 806 deaths. Males represented 62.3 % of the patients, and the average age was 51.2 ± 27.7 years. Almost all patients had devices: central line (63.6 %), foley catheters (52.7 %), or mechanical ventilation (50.4 %). More than 70 % of the outbreaks occurred in intensive care units and two-thirds were manifested as infection. The main device-associated infections were central line-associated bloodstream infection (38.5 %) and ventilator-associated pneumonia (39.0 %). The main pathogens were Candida auris (29.9 %), Klebsiella spp. (24.5 %), Acinetobacter baumanni (19.6 %) and Pseudomonas spp. (7.7 %). More than 60 % of the bacteria were resistant, including Carbapenem-resistant Enterobacteriaceae (32.5 %), multidrug-resistant bacteria (26.4 %), and Extended spectrum B-lactamases (23.0 %). Approximately 33.7 % of the patients died, 24.1 % cured, 19.3 % transferred, and 17.0 % discharged. Conclusions: Outbreaks caused by Gram-negative bacteria and Candida auris remain the main challenge in Saudi hospitals, representing 90 % of the outbreaks. The high resistance of causative pathogens and high associated mortality underscore the importance of strict implementation of infection control measures.